Afropean Biblical Studies : Constructing a Nigerian/British Women's Hermeneutic - Obamakin, Olabisi (Biblical Studies, Ancient Near East and Early Christianity E-Books Online, Collection 2026., 2026)
Step into the pioneering field of Afropean Biblical Studies. This book constructs a Nigerian/British women's hermeneutic that reshapes how we read the New Testament, blending feminist, postcolonial, and decolonial approaches. In this book, readers will meet the author through her autobiographical reflections, which, alongside rich literary and cultural insights, illuminate fresh readings of biblical characters-like Herodias's daughter (Mark 6:17-28; Matthew 14:3-12) and the woman who washed Jesus' feet (Luke 7:36-50)-and engage popular contemporary novels, including Bernardine Evaristo's Girl, Woman, Other . Original, innovative, and methodologically bold, it challenges Western-dominated scholarship and opens new horizons in biblical interpretation.